Visualization of Melanosome Dynamics within Wild-Type and Dilute Melanocytes Suggests a Paradigm for Myosin V Function In Vivo - Wu, Xufeng (The Rockefeller University Press, 1998)
Unlike wild-type mouse melanocytes, where melanosomes are concentrated in dendrites and dendritic tips, melanosomes in dilute (myosin Va(−)) melanocytes are concentrated in the cell center. Here we sought to define the role that myosin Va plays in melanosome transport and distribution. Actin filaments that comprise a cortical shell running the length of the dendrite were found to exhibit a random orientation, suggesting that myosin Va could drive the outward spreading of melanosomes by catalyzing random walks. In contrast to this mechanism, time lapse video microscopy revealed that melanosomes undergo rapid (∼1.5 μm/s) microtubule-dependent movements to the periphery and back again. This bidirectional traffic occurs in both wild-type and dilute melanocytes, but it is more obvious in dilute melanocytes because the only melanosomes in their periphery are those undergoing this movement. While providing an efficient means to transport melanosomes to the periphery, this component does not by itself result in their net accumulation there. These observations, together with previous studies showing extensive colocalization of myosin Va and melanosomes in the actin-rich periphery, suggest a mechanism in which a myosin Va–dependent interaction of melanosomes with F-actin in the periphery prevents these organelles from returning on microtubules to the cell center, causing their distal accumulation. This “capture” model is supported by the demonstration that (a) expression of the myosin Va tail domain within wild-type cells creates a dilute-like phenotype via a process involving initial colocalization of tail domains with melanosomes in the periphery, followed by an ∼120-min, microtubule-based redistribution of melanosomes to the cell center; (b) microtubule-dependent melanosome movement appears to be damped by myosin Va; (c) intermittent, microtubule-independent, ∼0.14 μm/s melanosome movements are seen only in wild-type melanocytes; and (d) these movements do not drive obvious spreading of melanosomes over 90 min. We conclude that long-range, bidirectional, microtubule-dependent melanosome movements, coupled with actomyosin Va–dependent capture of melanosomes in the periphery, is the predominant mechanism responsible for the centrifugal transport and peripheral accumulation of melanosomes in mouse melanocytes. This mechanism represents an alternative to straightforward transport models when interpreting other myosin V mutant phenotypes.